Implementasi Desain Grafis di Perpustakaan INSTIPER Yogyakarta - Mochammad Riski Destrianto (Perpustakaan Nasional, 2023)
The library plays a crucial role in assisting patrons in accessing the knowledge they need. The library needs to ensure that its collections and services are easily accessible and utilizable by patrons. One way to enhance the accessibility of the library, both in terms of services and collections, is by implementing graphic design. This article explores the implementation of graphic design in the INSTIPER Yogyakarta Library using a qualitative descriptive method, with observation and literature review as data collection methods. Based on data processing results, the researcher identified four library activities that utilize graphic design: 1. Signage design and library information production; 2. Development of teaching materials for faculty members; 3. Development of realia collections and arboretum; 4. Publishing. The graphic design products produced by the library are disseminated through various media, ranging from traditional notice boards, computer screens, social media, to the Learning Management System (LMS). The results of these graphic design products are also used for various purposes, including location navigation, branding, educational materials, promotion, and information reformatting.